UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL, AIR BUNCIS (Phaseolus vulgaris L.) DAN FRAKSI-FRAKSINYA TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Kristianto, Yosua Bayu; Sulistyarini, Indah; Suharsanti, Ririn (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2019)
Infection is a disease caused by the entry of a pathogenic microorganism in the body'stissues. One of the bacteria that can cause infection is Staphylococcus aureus. Beans are oneof the plants that contain alkaloids, flavonoids and saponins. Which is believed to inhibit thegrowth of Staphylococcus aureus bacteria. This study aims to determine the antibacterialactivity of extracts and its fraction on the growth of Staphylococcus aureus bacteria atconcentrations of 5%, 10%, and 15%. Bean powder was remacerated with 70% ethanol for 3days, and the extract obtained was subjected to fractionation with n-hexane, ethyl acetate,and water using a separating funnel. The antibacterial activity on the extract and eachfraction was made with a concentration of 5, 10, and 15% using the agar well method.Dimethyl Sulphoxide (DMSO) as a negative control and ciprofloxacin 0.005% as a positivecontrol. Antibacterial activity was measured using the inhibition zone diameter of bacterialgrowth. The results showed that the average inhibition zone diameter of ethanol extract, nhexanefraction and ethyl acetate fraction of beans at concentration of 5%, 10% and 15%respectively were of 0.842; 0.935 and 1.042 cm. The n-hexane fraction is 0.595; 0.787; and0.947 cm. Ethyl acetate fraction of 0.926; 1,008 and 1,049 cm. Whereas the water fractiondoes not provide antibacterial activity. The contact bioautography test results showed thatalkaloid compounds, flavonoids and saponins were able to inhibit the growth ofStaphylococcus aureus bacteria. The conclusions of this study are ethanol extract, n-hexanefraction, and ethyl acetate fraction of chickpeas having antibacterial activity againstStaphylococcus aureus bacteria, but the water fraction has no antibacterial activity against S.aureus; there was a significant difference (p <0.05) between the extract, n-hexane fraction,ethyl acetate fraction and water fraction.